Students’ perception on learning TOEFL structure and written expression using Youtube video and Instagram - Suriyah, Eni (LPPM Universitas Mercu Buana Yogyakarta, 2022)
TOEFL is English language testing that is very important to measure someone’s ability as high result of TOEFL measurement brings many advantages for future career. Integration of TOEFL Teaching with technology would be amazing at this era, 21st century. The aims of this study are to know students’ perception on learning TOEFL using Youtube video and Instagram, how the process of learning TOEFL Structure and Written Expression using Youtube and Instagram, and to know whether the students understand the materials or not. Researcher employed qualitative approach using phenomenology design. Data collection techniques are interview, observation, documentation from Instagram account used in the class. The result revealed that students’ perception on learning TOEFL Structure and Written Expression using Youtube and Instagram is positive and good. They were happy and understood the materials that they have watched from Youtube. The learning processes consist of four stages, namely the lecturer opens a class in the what's app group, students are asked to open Instagram @misteringlish.id to find out the Youtube video used and practice questions, students watch Youtube videos, and students do practise questions. They understand the material and be able to get good and high score when they do more than 13 questions. In conclusion, the result of this study support that Youtube and Instagram are effective to be used in learning TOEFL structure and written expression and it improves students’ understanding.